The Figures of Speech in the Lao Revolutionary Songs - DUANGCHAN, Boy; PAPAPHAN, Bualy; NANTHAVONG, Vandthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aimed to study the usage of figures of speech in Lao Revolutionary Song. There were 96 songs used as a sample. Sujitra Jongsatitwatana’s criterion used in this research included 9 figures of speech: simile, metaphor, synecdoche, metonymy, personification, hyperbole, onomatopoeia, oxymoron and paradox. From the research, it was found that 9 figures of speech: simile, metaphor, synecdoche, metonymy, personification, hyperbole, onomatopoeia, oxymoron and paradox, were used in Lao Revolutionary Songs a simile was most frequently used, 50 phrases were found being used in the song, showing 25.12%. Next, 49 phrases of metaphor were found being used in the lyrics, showing 24.62 %. The 31 phrases of Hyperbole were found being used, showing 15.58%. The 20 phrases of Onomatopoeia were found being used, showing 10.05%. The 16 phrases of Metonymy were being used, showing 8.04 %. The 15 phrases of Personification were being used, showing 7.53 %. The 9 phrases of Oxymoron were being used, showing 4.52%. The 5 phrases of Synecdoche were being used, showing 2.51 %. Finally, the only 4 phrases were being used, showing 2.01 %.